2023
DOI: 10.1126/sciadv.ade4443
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuronal circuits promote disease progression in cancer

Abstract: The molecular and functional contributions of intratumoral nerves to disease remain largely unknown. We localized synaptic markers within tumors suggesting that these nerves form functional connections. Consistent with this, electrophysiological analysis shows that malignancies harbor significantly higher electrical activity than benign disease or normal tissues. We also demonstrate pharmacologic silencing of tumoral electrical activity. Tumors implanted in transgenic animals lacking nociceptor neurons show re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…Given that rabies virus does not label all synaptic inputs of starter cells 68,69 , our observation may still represent an underestimation. Our findings thus significantly expand the notion that tumor cells may be innervated and regulated by myriad neuronal subtypes [70][71][72][73] , such as those comprising neuromodulatory systems 74,75 that signal through metabotropic neurotransmitter receptors. Given the ability of glioma to bidirectionally interact with neuronal circuits 19,20,76,77 combined with established roles of diffuse neuromodulatory projections in memory and behavior 43,78 , our discoveries also provide a foundation to investigate whether feedback to neurons that innervate GBM cells might explain generalized patient symptoms such as cognitive dysfunction, sleep disturbances, seizures, or behavioral deficits that affect quality of life [79][80][81][82] and to develop corresponding therapeutic interventions.…”
Section: Discussionsupporting
confidence: 67%
“…Given that rabies virus does not label all synaptic inputs of starter cells 68,69 , our observation may still represent an underestimation. Our findings thus significantly expand the notion that tumor cells may be innervated and regulated by myriad neuronal subtypes [70][71][72][73] , such as those comprising neuromodulatory systems 74,75 that signal through metabotropic neurotransmitter receptors. Given the ability of glioma to bidirectionally interact with neuronal circuits 19,20,76,77 combined with established roles of diffuse neuromodulatory projections in memory and behavior 43,78 , our discoveries also provide a foundation to investigate whether feedback to neurons that innervate GBM cells might explain generalized patient symptoms such as cognitive dysfunction, sleep disturbances, seizures, or behavioral deficits that affect quality of life [79][80][81][82] and to develop corresponding therapeutic interventions.…”
Section: Discussionsupporting
confidence: 67%
“…MOC2-7 cells are HNSCC cancer cells derived from a CXCR3 null mouse under a C57BL6 background 29 . Their implantation in male mice results in dense innervation of tumors with nociceptor neurons 38,39 . To define the timing of tumor innervation, wildtype male mice were orthotopically implanted with MOC2-7 cells in the oral cavity, and tumors were collected on days 4-, 10-, and 20-days post-implantation.…”
Section: Resultsmentioning
confidence: 99%
“…In high-grade serous ovarian cancer and head and neck squamous cell carcinoma, a significant increase in nerve puncta has been confirmed, and the authors found that substance P expressed from wheat germ agglutinin (WGA) + nerve fibers stimulates the proliferation and migration of tumor cells through the neurokinin (NK)-1 receptor. In this model, blockade of neural signaling through the deletion of TRPV1 + sensory nerve or pharmacological inhibition of these signaling using fosaprepitant or lidocaine prevented tumor growth and metastasis ( 56 ). These results indicate that sensory nervous system is a strong contributor to cancer progression rather than being a bystander ( 55 ).…”
Section: Autonomic Regulation Of Tumor Growthmentioning
confidence: 99%